ANALISIS TERHADAP PUTUSAN PERKARA SYIQAQ DI PENGADILAN AGAMA SUNGAI PENUH - Arpan Zaman (Ensiklopedia of Journal, 2021)
This research aim at analyzing of syiqaq in marriage and how to know the syiqaq case in Pengadilan Agama Sungai Penuh and to know reason from who suspect of syiqaq, explain about the vis suggestion and to explain investigation process of syiqaq case in Pengadilan Agama Sungai Penuh. The benefit of research can be seen from teoritic aspect, academic and practice. Methode of the research used were yuridical and sociological approach. Conclusion of the research were what and how to find the bright clarity of the problems in the marriage relationship of syiqaq. From the analysis of  syiqaq case section 76 verse 1 UU NO 7 1989 can be seen that the verdict syiqaq depend on the testimony of witnesses. In Pengadilan Agama Sungai Penuh, it does not stipulate direcly that syiqaq be one strong reason for divorce because there are still a lot of statements from witnesses to the way of peace as stated in several laws and regulations.